Peculiarities of «delta» to «star» equivalent impedances conversion in pi- and T-shaped filter structures - A.V. Baranov; A.L. Kozikov (Физика волновых процессов и радиотехнические системы, 2019)
The peculiarities of delta to star equivalent impedances conversion are noted in pi- and T-shaped filter structures. They are taken into consideration for design filters and oscillators resonators. The physical limitations are determined for structures parameters, which lead to these peculiarities. The conversion frequencies are obtained for - and T-shaped filter structures, where delta to star equivalent impedances transformation is fulfilled.